(untitled) (Medicine Today, 2017)
The aim of this study is to assess the outcome of Pedicled extended Lateral arm flaps (PELAF) for coverage of defects of the hand and forearm. 09 patients were included in this study from January, 2005 to February 2009. Patients with hand defects with or without extension up to the forearm, resurfaced with this flap, were reviewed for this case series. Eight flaps were cross arm, i.e. for defects in the contra lateral hand and 01 was used to cover the cubital fossa of the same limb. Ages of the patients ranged from 23-46 years, 01 female and 08 male. 08 patients were diabetic while 01 was non diabetic. Nine cases were managed by extended lateral arm flap or a standard lateral forearm flap. Postoperative periods of all the patients were uneventful. Then pedicle was divided after 3 weeks for the cross arm flap group. For patients with wounds on the hand, wrist and forearm pedicled lateral and extended lateral arm flap provides an excellent thin, supple and reliable option for coverage. Cross Lateral arm flap is one of the few local options available with good colour and contour match and requires no sacrifice of major blood vessel. Medicine Today 2017 Vol.29(2): 9-12